Spatial Variability of the Physicochemical Properties of Fallow Soils Formerly Used for Perennial Crops (Cocoa and Coffee) In the Department of Daloa (Central West of Côte d’Ivoire) - Bony, Kakou; Zro, Ferdinand Gohi Bi; Guéi, Martinez Arnauth (European Journal of Applied Sciences, 2023)
At the present time of recovery of soils formerly used for perennial crops that have fallen into decline in the Department of Daloa, located in the central-western part of Côte d’Ivoire, a West African country, there is a need to assess the fertility potential of these soils in order to avoid a possible rapid failure of the new crops envisaged. Thus, the present study aims to identify the variables determining the fertility of these soils, particularly those formerly used for cocoa and coffee production, and to explain the spatial variability of these properties at the scale of the study area. To this end, a quantitative characterisation of the physico-chemical composition of the soils of seven plots that had been abandoned for at least ten years was carried out. Soil samples were taken from three soil pits dug at each site in three layers for laboratory analysis. The soil properties resulting from these analyses were subjected to a variance analysis at the 5% threshold and a determination of the coefficients of variation. The results obtained made it possible to highlight the soil parameters that vary to a greater or lesser extent from one site to another, but which are also crucial for the management of the fertility of the soils studied.